2018
DOI: 10.2147/cmar.s163209
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association pathway analysis to identify candidate single nucleotide polymorphisms and molecular pathways associated with TP53 expression status in HBV-related hepatocellular carcinoma

Abstract: BackgroundThe aim of this investigation was to identify candidate single nucleotide polymorphisms (SNPs) and molecular pathways associated with tumor protein p53 (TP53) expression status in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC), clarify their potential mechanisms, and generate SNP-to-gene to pathway hypothesis.Materials and methodsIdentify candidate Causal SNPs and Pathways (ICSNPathway) was used to perform pathway analysis based on the results of our previous genome-wide association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Of the 12 SNPs reported in HBV-related HCC GWASs, rs2647073 and rs3997872 near HLA-DRB1 were found to be significantly associated with the risk of HBV-related LC, which suggested that genetic variants associated with HBV-related hepatocarcinogenesis may already play an important role in the progression from CHB to LC [43]. A recent study reported new SNPs at HLA-DRB 1 (rs35445101) associated with TP53 expression status in HBV-related hepatocellular carcinoma [30].…”
Section: Hla Class II Allele Polymorphism and Hbv Infection Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 12 SNPs reported in HBV-related HCC GWASs, rs2647073 and rs3997872 near HLA-DRB1 were found to be significantly associated with the risk of HBV-related LC, which suggested that genetic variants associated with HBV-related hepatocarcinogenesis may already play an important role in the progression from CHB to LC [43]. A recent study reported new SNPs at HLA-DRB 1 (rs35445101) associated with TP53 expression status in HBV-related hepatocellular carcinoma [30].…”
Section: Hla Class II Allele Polymorphism and Hbv Infection Outcomesmentioning
confidence: 99%
“…Chang et al found that rs9276370 (HLA-DQA 2 ), rs7756516, and rs7453920 (HLA-DQB 2 ) are significantly associated with persistent HBV infection, especially the "T-T" haplotype composed of rs7756516 and rs9276370 that is more prevalent in severe disease subgroups and associated with nonsustained therapeutic response in male Taiwan Han Chinese individuals [49]. A nearest study reported four new SNPs at HLA-DQB 1 (rs1130399, rs1049056, rs1049059, and rs1049060) associated with TP53 expression status in HBV-related HCC [30].…”
Section: Hla Class II Allele Polymorphism and Hbv Infection Outcomesmentioning
confidence: 99%
See 3 more Smart Citations